EFEKTIVITAS LATIHAN WIDE GRIP PUSH UP TERHADAP KEMAMPUAN SERVIS FOREHAND DALAM PERMAINAN BULUTANGKIS PADA KLUB PB. RUDY’S MATARAM TAHUN 2016 - Soemardiawan Soemardiawan (Jurnal Ilmiah Mandala Education (JIME), 2016)
Badminton players are a very complex game, where badminton games consist of several very varied basic techniques. Every player should be able to master badminton skills, in order to be able to excel, but at club PB Rudy's Mataram, still lack ability in long service, there are still many players who only serve without proper technique. Problem formulation in this research is whether there is Effectiveness Exercise Wide Grip Push Up Against Service Ability Forehand In Badminton Game At Rudy's PB Club Year 2016 ?. Research Objectives Want to know whether or not the effectiveness of Wide Grip Push Up Exercise Against the Ability of Forehand Service in Badminton Game at PB PB Rudy's Club Year 2016. The research design used is the experiment research "One-Group Pretest-posttest Desaign". This experiment still has external variables that affect the formation of the dependent variable. The implementation of this design is by giving treatment (treatment), in the form of Wide Grip Push Up exercise on the subject within a certain time, the measurement of Service Forehand Capability is done with lob service test instrument (sevis long) done before and after treatment given. The population used is 12 players, the sampling technique using population study. And the result of this condition research is supported by t-test which produce t-count larger than t-table (8.028> 2.201) so that the hypothesis Zero (Ho) is rejected and hypothesis (Ha) accepted which reads: "There is Effectivity Wide Grip Exercise Push Up On Forehand Service Ability In Badminton Game At Rudy's PB Club of the Year 2016